2023
DOI: 10.1039/d3nr01113e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of violet phosphorus with large lateral sizes to facilitate nano-device fabrications

Abstract: The violet phosphorus has been proven to be the most stable phosphorus allotrope and attracted much attention recently. The growth of violet phosphorus with large lateral sizes is crucial to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We conducted a comprehensive series of tests to ensure the optimal performance of the VPNS used in our experiments. Scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), and X-ray diffraction (XRD) (see Figure c,d) analyses revealed that the violet phosphorus and VPNS exhibited high quality. , The lattice spacing and intersecting angle both closely match those of the (110) and ( ) lattice planes in the crystallographic structure of violet phosphorus single crystals, as determined by single-crystal X-ray diffraction (XRD). Analogous to the XRD patterns, strong stretching vibration modes of [P9] cages at 293 cm –1 (S 1 [P9] ) and 353 cm –1 (S 2 [P9] ), the stretching mode of [P8] at 373 cm –1 (S 2 [P8] ), and the tangential stretching mode of [P9] along the tubular axis at 471 cm –1 ( T g ) were readily observed in violet phosphorus (Figure e).…”
Section: Resultsmentioning
confidence: 86%
“…We conducted a comprehensive series of tests to ensure the optimal performance of the VPNS used in our experiments. Scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), and X-ray diffraction (XRD) (see Figure c,d) analyses revealed that the violet phosphorus and VPNS exhibited high quality. , The lattice spacing and intersecting angle both closely match those of the (110) and ( ) lattice planes in the crystallographic structure of violet phosphorus single crystals, as determined by single-crystal X-ray diffraction (XRD). Analogous to the XRD patterns, strong stretching vibration modes of [P9] cages at 293 cm –1 (S 1 [P9] ) and 353 cm –1 (S 2 [P9] ), the stretching mode of [P8] at 373 cm –1 (S 2 [P8] ), and the tangential stretching mode of [P9] along the tubular axis at 471 cm –1 ( T g ) were readily observed in violet phosphorus (Figure e).…”
Section: Resultsmentioning
confidence: 86%